Consumer Attitudes Toward Human-Like Avatars in Advertisements: The Effect of Category Knowledge and Imagery. Issue 3 (3rd July 2018) - Gammoh, Bashar S.; Jiménez, Fernando R.; Wergin, Rand
ABSTRACT: Despite the importance and the growing use of avatars in online and offline advertising, investigations on the effectiveness of avatar-based advertising remains scant. This article attempts to narrow this gap by examining several factors that influence consumers' evaluations of human-like avatar-based ads. Based on mental schema theory, the authors theorize that avatars elicit categorization tension, a feeling of incongruence between avatar and expected human features. This tension is reflected in negative attitudes toward the ad and low purchase intention. Two experiments supported these contentions and demonstrated how product category knowledge and imagery moderate these effects. This investigation contributes to theory by employing a mental schema framework to explain and predict how and when consumers form positive evaluations of human-like avatar-based ads. The research findings also offer several recommendations for advertising professionals. The findings suggest that human-like avatars are more likely to generate negative evaluations among novice or less knowledgeable consumers. To minimize this effect, advertisers can encourage consumers to imagine the consumption experience.